THE EFFECT OF HUMAN CAPITAL ON FINANCIAL PERFORMANCE WITH CORPORATE SUSTAINABLE GROWTH AS A MODERATING VARIABLE - Selfiani, Selfiani (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
In facing the era of globalization which is marked by the rapid development of the economy in Indonesia today, companies can further improve their performance in order to survive in the face of economic developments that are always changing rapidly and dynamically. In the face of an economy that is always changing rapidly and dynamically, companies can also grow companies in a sustainable manner. To test and analyze the influence of Human Capital on Financial Performance. To test and analyze the effect of Corporate Sustainable Growth on moderating the relationship between Human Capital and Financial Performance. The population in this study are Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX). A sample of 35 companies from 100 Kompas100 Index companies listed on the Indonesia Stock Exchange in 2021. This study uses a quantitative approach and tools for hypothesis testing using SPSS software. With classical assumption test, normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results of this study are multiple regression analysis that human capital has a greater influence on financial performance than the company's sustainable growth. Human capital has a positive effect on financial performance, Corporate Sustainable Growth strengthens the relationship between Human Capital and Financial Performance.